Success Stories From Patient’s with Stroke Recurrence Prevention: A Qualitative Study - Heny Suseani Pangastuti; Yeni Rustina; Sudijanto Kamso; Ratna Sitorus (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Recurrence is an issue encountered by patients with stroke in Indonesia. Stroke recurrence might occur due to the patient’s inability to perform secondary prevention, particularly the non-pharmacological one, by changing their lifestyle. Many patients with stroke are known to survive longer with no recurrence. This research aimed to explore the experience of the patient with stroke and success in stroke recurrence prevention. Methods: This was a qualitative study using a descriptive exploratory method. Eight post-stroke patients who met the inclusion criteria participated in this research. The data were collected using an in-depth interview. The data were then analyzed using Giorgi method. Results: From the data analysis, it was found these stroke patients could survive without experiencing any recurrence in a certain period of time thanks to some reasons which could be classified in four themes, namely: 1) having a good food management habit, 2) having a good physical exercise/activity habit, 3) using traditional medicine instead of conventional medicine, and 4) there are some factors influencing successful management of stroke recurrence prevention. Conclusions: Patients with stroke, have a good experience and good habits to prevent their stroke recurrence, but they still have a misperception about convention medicine. This result shows the importance of the ability to manage recurrence risk factors in post-stroke patients, to prevent them from having a recurrence. Need further research on the use of traditional medicine in a stroke patient.